Molecular phylogeny of the genus Dorometra Clark, 1917 (Crinoidea: Comatulida: Antedonidae): a new genus and new insights for future taxonomic revisions of Antedonidae. Issue 1 (31st December 2023) - Virgili, R.; Poliseno, A.; Fujita, T.; Pratama, G. A.; Fernández-Silva, I.; Reimer, J. D.
Abstract : Dorometra Clark, 1917 (Comatulida: Antedonidae) is an Indo-Pacific genus of small-sized cryptic feather stars currently comprising nine species. The monophyly of this crinoid genus has been widely questioned, although only few studies have investigated the phylogeny of Antedonidae in depth. In this study we used an integrated approach combining molecular phylogenetic, morphology, and multivariate analyses to clarify the taxonomic placement of the genus Dorometra within family Antedonidae. Eight of the nine known species of the genus collected from Australia to the Sea of Japan were included in analyses. Phylogenetic analyses using sequences from two mitochondrial (COI, 16S) and one nuclear (28S) genes demonstrate that Dorometra is polyphyletic, and its species are divided into three main clades, which are spread within other Antedonidae. As a result, we herein describe Nesometra gen. nov. Four different species delimitation methods on single and multi-locus alignments also showed higher diversity than previously thought. In particular, our results highlighted the presence of cryptic diversity within the species Dorometra nana (Hartlaub, 1890) in geographically close localities within southern Japan. By multivariate analysis of morphological matrix, we confirmed the homoplasy and plasticity of the taxonomic characters used in the description of Dorometra species, providing a path forward for the general taxonomic revision of this genus and of Antedonidae and related families. http://zoobank.org/urn:lsid:zoobank.org:pub:DB7C239C-5CA0-485B-B4A8-205288FC4080